VARIOUS MANIFESTATIONS OF TRACHOMA IN INTERNALLY DISPLACED RURAL POPULATION - A FREE EYE CAMP BASED SURVEY - Babar, Zahir ud Din; Khan, Muhammad Saim; Murtaza, Bilal; Khattak, Rafiq Ahmad; Shah, Shahrukh; Shahzad, Khurram (Journal of Ayub Medical College Abbottabad, 2018)
Background: the objective of the study is to observe frequency of various clinical manifestations of trachoma in rural population. This observational study was conducted at Khalifa Gul Nawaz Teaching Hospital (KGNTH), Bannu, Pakistan from April 2016 to Jan 2017. Methods: Patients visiting for ocular complaints underwent initial screening that included demographic details and documentation of unaided as well as best corrected visual acuity (BCVA) which was followed by detailed slit lamp examination of anterior segment including eversion of upper lid for assessment of changes in upper tarsal conjunctivas by consultant ophthalmologist. A total of 648 patients who had clinical presentation of trachoma were included in the study. Patients who had other forms of conjunctivitis, trichiasis, entropion, corneal opacification and vascularization due to causes other than trachoma were excluded. Patients were categorized according to age in three groups (Group 1-3) and according to stages of trachoma in five groups (TF, TI, TS, TT and TO). Results: Six hundred and forty-eight (648) were examined in this cross-sectional survey with a mean age of 14.3+14.2 years. Mean unaided visual acuity and BCVA of the patients was 0.12+.24 and 0.07+0.18 respectively. Groups-1 comprised of 86.7% of the patients and stage TF of trachoma was the most prevalent stage accounting for 70.06% of the patients. Conclusion: Trachoma is a serious community health problem with various clinical manifestations in different age groups. Awareness and educational programs are required to be conducted in schools and vocational training centers regarding its mode of transmission and control. Keywords: Trachoma; Prevalence; Follicular conjunctivitis